Β-Lactamase In Acinetobacter Species: A Global Threat - P. ANITHA,; SUDHA RAMAIAH, (International Journal of Pharma and Bio Sciences, 2011)
Acinetobacter species are ubiquitous in nature. The members of genus Acinetobacter causes nosocomial infections. Acinetobacter spp. has emerged as globally challenging pathogen due to multiple antibiotic resistant. Major concern is that it shows resistance to all available β-lactam antibiotics classes such as carbapenems and third-generation cephalosporins. Acinetobacter spp. can survive on both natural and hospital environment, especially in intensive care unit and have been identified in military camps and predominantly isolated from burns and wounds unit. It is demonstrated that mobile genetic elements are responsible for the clonality spreads. Indeed, new antibiotics are much needed for the treatment since there are only limited options left for the clinicians. This review details about the nature, spread, clinical significance, detection method, current antibiotic regimen and highlights its public health threat.